IMPLEMENTASI PROGRAM KELAS PAJAK SEPUTAR E- FAKTUR DAN PKP “KANG KASEP DALAM RANGKA MENINGKATKAN KEPATUHAN PENGUSAHA KENA PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BEKASI UTARA - Harjo, Dwikora; Aprianti, Nur; Kumala, Ratih (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The evolving taxation system at the North Bekasi Primary Tax Office has led to the creation of the Tax Class Program on E-Invoice and Taxable Entrepreneur "Kang Kasep" aimed at enhancing the tax compliance of taxable entrepreneurs who are not yet fully aware of their rights and obligations in the reporting and payment of periodic VAT, thereby reducing the issuance of Tax Invoices and providing certainty to taxable entrepreneurs. This research aims to discover and analyze the implementation of the Tax Class Program on E-Invoice and Taxable Entrepreneur "Kang Kasep" in enhancing tax compliance among itaxable entrepreneurs at the North Bekasi Primary Tax Office, as well as the obstacles and efforts in implementing the Tax Class Program on E-Invoice and Taxable Entrepreneur "Kang Kasep" This research employs a descriptive qualitative research method. Data collection methods include interviews. observations, and documentation. The author utilizes the Policy Implementation Theory according to Van Metter & Van Horn (Mulyadi, 2015 72). The results indicate that the Tax Class Program on E-Invoice and Taxable Entrepreneur "Kang Kasep" has been running quite optimally although there are still challenges with taxable entrepreneurs who are not yet aware of the "Kang Kasep" Tax Class Program Additionally some taxable entrepreneurs still require more extensive socializationregarding the implementation of this program.